Evaluación del efecto de la intensidad de labranza en la formación de costra superficial de un oxisol de sabana en los Llanos Orientales de Colombia : II. Caracterización física en superficie - Galvis, JH; Amézquita Collazos, Edgar; Madero, E (2007)
The outlined methodology in this article allowed correlating soil sealing and soil physical properties as structural stability, infiltration velocity, soil loss erosion, run off, normal and torsion resistance and aggregate distribution. The output showed that improved pastures after eight years of sowing produced a relatively positive response to soil erosion and mechanical strengths. But periodic farming and fertilization that are required for corn production although resulted in good seed bed preparation and created a good environment to store moisture, it allowed an increase of soil erosion and decrease of soil structure stability.